Oxidation of thin film at the air-water interface of cloud droplets using REAL atmospheric aerosol from polar, marine and urban sources - Professor Martin King; Miss Rosalie Shepherd; Dr Andy Ward; Professor Adrian Rennie; Dr Maxmilian Skoda (ISIS Facility, 2016)
The Earth's climate is strongly influenced by clouds. The oxidative processing of pollutants in clouds affects droplet size and optical properties, important effects. Common cloud pollutants are naturally occurring organic surfactants forming organic films on the droplet, The climatic effect depends on the rate of atmospheric oxidation of these films and whether any product film forms. In this work we will study the kinetics of hydroxyl radical with insoluble surfactants from samples from Antarctica, mid-Atlantic and Urban London. Specifically we will (a) demonstrate that an aqueous cloud oxidant, the OH radical, can oxidise a real atmospheric organic film with different provenances, b) calculate the effect of the reaction on the hygroscopic properties of a cloud droplet and demonstrate removal of the organic film may cause a cloud to evaporate (c) Support an STFC futures grant.